Effect of surface treatments on implant crown retention - Göknil Ergün Kunt; Gözlem Ceylon; Nergiz Yilmaz (Elsevier, 2010)
There are several surface treatment methods to improve the bond strength between dental materials. The purpose of this study was to examine the effect of different surface treatments on the tensile bond strength of single crowns on Implant Direct abutments cemented with resin cement. Materials and methods: In total, 28 Screw Plant implants and abutments were divided into four study groups: I, control; II, sandblasted abutment and crown; III, non-sandblasted abutment and alloy primer applied to a sandblasted crown; and I V, alloy primer applied to a sandblasted abutment and crown. Twenty-eight crowns were cemented to abutments of implants, and a uniaxial tensile force was applied to the crowns using a universal test machine until cement failure occurred. Retention values were statistically analyzed. Results: All mean retention values significantly differed among groups. While the alloy primer applied to the sandblasted castings and abutments showed the highest mean value (564.73 ± 13.66 N), the control group showed the lowest mean value (357.65 ± 12.89 N). Sandblasting was not as effective as application of an alloy primer (P = 0.05). Conclusion: Sandblasting is an effective method to increase the bond strength. Sandblasting plus alloy primer application is a very effective method of increasing the bond strength, and these groups significantly differed from each other.